2016
DOI: 10.3311/ppci.8498
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Warm Mix Asphalt Mixtures with Recycled Asphalt Pavement

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…In the literature, many of the indices obtained from the SGC compaction curves have been reported and used to evaluate the asphalt mixture compactability, and the compaction energy index (CEI) and traffic densification index (TDI) were used generally [23,25], which were determined using the compaction curve data (as illustrated in Figure 1) for measuring compaction energy [26,27]. The CEI index focused on the results from cycle 8 until a DC of 92% was reached, which corresponded to the minimum density for traffic opening [28].…”
Section: • Compaction Energy Indexmentioning
confidence: 99%
“…In the literature, many of the indices obtained from the SGC compaction curves have been reported and used to evaluate the asphalt mixture compactability, and the compaction energy index (CEI) and traffic densification index (TDI) were used generally [23,25], which were determined using the compaction curve data (as illustrated in Figure 1) for measuring compaction energy [26,27]. The CEI index focused on the results from cycle 8 until a DC of 92% was reached, which corresponded to the minimum density for traffic opening [28].…”
Section: • Compaction Energy Indexmentioning
confidence: 99%
“…Chemical WMA additive is a combination of cationic surfactants and organic additive-based rheology modifier. The additive chemically modifies the bitumen and obtains active adhesion force that improves coating of aggregates with bitumen [18][19][20][21][22][23].…”
Section: Two Bitumen Modifier Types Elastomeric Type -Styrenementioning
confidence: 99%
“…In the last decade, some investigations on the use of RAP in WMA [7,[9][10][11] and HWMA have been conducted. In the case of HWMA with a high RAP content, only a few studies have been reported.…”
Section: Mixturementioning
confidence: 99%